Elfquest: the final quest (2014), volume 2 ebook The final quest volume 2. - Pini, Richard (Elfquest: The Final Quest (2014), 2016)
Sunstream, son of Wolfrider chief Cutter Kinseeker, finally fulfills his destiny and becomes the psychic link among all the elfin tribes scattered across the World of Two Moons. At long last, the seeds planted 20,000 years ago in the original, classic quest can come to fruition. But a devastating secret, hidden in plain sight, is moving into the light, and it will affect the elfin race forever. Volume 2 collects Wendy and Richard Pini's issues #7–#12 of The Final Quest, the newest adventures of the Wolfriders!